“TAXEMIC AND PRAGMATIC APPROACHES TO COMPOSITE SENTENCES: FUNCTIONAL SENTENCE PERSPECTIVE, DISCOURSE ANALYSIS, AND PUNCTUATION IN MODERN ENGLISH” (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article provides an integrated linguistic analysis of composite sentences in Modern English through five complementary perspectives: structural (compound, complex, and compound-complex sentences), taxemic (formal signals and clause-linking mechanisms), functional sentence perspective (theme–rheme organization and communicative dynamism), pragmatics (speaker intention, politeness, and contextual meaning), discourse analysis (cohesion and coherence across texts), and punctuation (semantic and emphatic functions). The study demonstrates how these theoretical frameworks interact and collectively influence meaning, emphasis, and communicative effect within composite constructions. Each section includes theoretical explanation, analytical interpretation, and practical examples to ensure clarity and applicability to linguistic research. The work contributes to English syntax studies by offering a multidimensional model for interpreting composite sentences beyond their structural form, highlighting their communicative and discourse-level significance.